Sentient Enterprise The Evolution of Business Decision-making. - Ratzesberger, Oliver; Sawhney, Mohanbir (John Wiley & Sons Inc, 2017)
Mohan and Oliver have been very fortunate to have intimate views into the data challenges that face the largest organizations and institutions across every possible industry-and what they have been hearing about for some time is how the business needs to use data and analytics to their advantage. They continually hear the same issues, such as: -We're spending valuable meeting time wondering why everyone's data doesn't match up.-We can't leverage our economies of scale while remaining agile with data.-We need self-serve apps that let the enterprise experiment with data and accelerate the development process.-We need to get on a more predictive curve to ensure long-term success. To really address the data concerns of today's enterprise, they wanted to find a way to help enterprises achieve the success they seek. Not as a prescriptive process-but a methodology to become agile and leverage data and analytics to drive a competitive advantage. You know, it's amazing what can happen when two people with very different perspectives get together to solve a big problem. This evolutionary guide resulted from the a-ha moment between these two influencers at the top of their fields-one, an academic researcher and consultant, and the other, a longtime analytics practitioner and chief product officer at Teradata. Together, they created a powerful framework every type of business can use to connect analytic power, business practices, and human dynamics in ways that can transform what is currently possible.